2017
DOI: 10.1007/s00595-017-1529-3
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative imaging evaluation of pancreatic pathologies for the objective prediction of pancreatic fistula after pancreaticoduodenectomy

Abstract: In performing pancreaticoduodenectomy (PD) or when conducting clinical trials involving PD procedure, a universal platform for predicting the risk of postoperative pancreatic fistula (POPF) is indispensable. In this article, the most significant imaging studies that focused on the objective preoperative assessment of pancreatic pathologies in association with the occurrence of POPF after PD were reviewed. Several recently developed imaging modalities can objectively predict the occurrence of POPF after PD by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 68 publications
(90 reference statements)
0
5
0
Order By: Relevance
“…Several preoperative imaging indicators of POPF risk have been identified (4)(5)(6)(7)(8), including morphologic features of the pancreatic stump (eg, thickness, area, main pancreatic duct [MPD] diameter), signal intensity at T1-weighted imaging, apparent diffusion coefficient (ADC), and fat fraction. These parameters are used to evaluate the morphologic characteristics or to establish a correlation with histologic changes (eg, fibrosis) of the pancreatic stump (9,10).…”
mentioning
confidence: 99%
“…Several preoperative imaging indicators of POPF risk have been identified (4)(5)(6)(7)(8), including morphologic features of the pancreatic stump (eg, thickness, area, main pancreatic duct [MPD] diameter), signal intensity at T1-weighted imaging, apparent diffusion coefficient (ADC), and fat fraction. These parameters are used to evaluate the morphologic characteristics or to establish a correlation with histologic changes (eg, fibrosis) of the pancreatic stump (9,10).…”
mentioning
confidence: 99%
“…Guo et al [ 25 ] reported that the texture of pancreas, size of the main pancreatic duct, portal vein invasion and confirmed pathology are the risk factors of postoperative PF. Tajima et al [ 26 ] summarized that preoperative imaging evaluation of pancreatic pathologies would be also beneficial for stratifying. Not surprisingly, systemic inflammatory markers such as neutrophils, lymphocytes, platelets, CRP, albumin, and biomarkers may help predict postoperative PF.…”
Section: Discussionmentioning
confidence: 99%
“…Soft pancreatic parenchyma is the most widely accepted risk factor ( 28 ). Although the mechanism by which FP promotes the occurrence of POPF has not been elucidated, some studies have proposed a possible theory for its pathogenesis ( 29 ): First, during pancreatic and intestinal anastomosis reconstruction, a soft pancreas is more susceptible to ischaemia and injury than a hard pancreas. When suturing between the fragile pancreatic parenchyma and the plasma or muscle layer of the intestine or stomach, the pancreatic ducts and parenchyma are more susceptible to laceration and injury.…”
Section: Discussionmentioning
confidence: 99%